ANALYSIS DOMINANT OF FACTORS INFLUENCE IN DECLINE COMPANY LIQUIDITY (Study PT.Pelabuhan Indonesia Surabaya Branch) - Ditarosa Taurista; Mustika Putri Fatimah A.; M. Khusni Mubarrok (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2018)
This study to determine the most dominant factor affect the decline of liquidity PT.Pelabuhan Indonesia Surabaya branch for five years (2010-2014) . The analy method used are source analysis and use of capital and cash flow as well as regression and correlation analysis. The result showed tthet the most dominant factor influenced the decrease of liquidity company ( Study Pt.Pelabuhan Indonesia Surabaya Branch) is a cash/bank factor. Technique of data collection is done by interview and interview in free and direct with competent parties. In addition, to obtain written data is done by requesting directly from the source in accordance with the needs.Based on the formulation of the problems and hypotheses that have been proposed, the method of analysis used in the discussion of this paper is the Regression and Correlation Analysis. Regression and correlation analysis is used to see the direction of the relationship and the influence of the relationship between each other, ie between the amount of net working capital (Y) as the dependent variable to the independent variable consisting of cash / bank (X1), accounts receivable (X2), inventory X3), and current liabilities (X4), used multiple linear regression analysis and Pearson correlation.